The Orient in Utrecht: Adriaan Reland (1676-1718), Arabist, Cartographer, Antiquarian and Scholar of Comparative Religion - Jaski, Bart; Lange, Christian; Pytlowany, Anna; van Rinsum, Henk J. (The History of Oriental Studies, 2021)
Adriaan Reland (1676-1718), Arabist, Cartographer, Antiquarian and Scholar of Comparative Religion covers the intellectual achievements of a remarkable man: Adriaan Reland, professor of Oriental languages (1701) and Hebrew Antiquities (1713) at the University of Utrecht from 1701 to 1718. Although he never travelled beyond the borders of his home country, he had an astonishingly broad worldview. The contributions in this volume illuminate Reland's many accomplishments and follow his scholarly trajectory as an Orientalist, a linguist, a cartographer, a poet, and a historian of comparative religions. Reland, although a devout Protestant, believed that religions should be examined objectively on their own terms with the help of reliable and authentic documents, which would dispel the prejudices of the past.. Readership: All interested in the history of philology and Oriental studies, study of religions and languages, and those interested in the dialogue between different religions, including Judaism, Christianity and Islam. The book, though in places specialized, is suitable for a wide readership, including BA- and MA-students.